Legal Protection Against Gharar in Sharia E-Commerce: A Consumer Law Analysis in Support of the SDGs - Fatihah Zakiya Aqmal; Muthoifin; Sana Ashraf (Universitas Muhammadiyah Surakarta, 2025)
Objective: By comparing the principles of Islamic law contained in the fatwa of DSN-MUI Number 146/DSN-MUI/XII/2021 and Law Number 8 of 1999 concerning Consumer Protection (UUPK), this study aims to analyze the legal protection provided to consumers against gharar (uncertainty) in sharia e-commerce transactions. Theoretical framework: used refers to fiqh muamalah, legal principles contained in the UUPK and in the DSN-MUI Fatwa, as well as the Sustainable Development Goals (SDGs), especially the 12th and 16th SDGs. Literature review: Few studies explicitly address the existence and forms of gharar in sharia e-commerce and its legal consequences, most of which still focus on consumer protection from a normative point of view only. Method: using normative legal analysis, with legislative, conceptual, and comparative approaches, and supported by literature studies. Results: show that although the Consumer Protection Law does not specifically mention the use of the term